2015
DOI: 10.1656/045.022.0118
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of an Invasive Shore Crab on Cape Cod, Massachusetts

Abstract: Invasive species can cause dramatic changes in the structure of intertidal communities. In some systems, however, abundance or impacts of invaders may peak 10-20 years after invasion and decline thereafter. Hemigrapsus sanguineus (Asian Shore Crab) has been established at Sandwich, MA, on the north side of Cape Cod, since the mid-1990s. This study documented population dynamics of the Asian Shore Crab and 3 species of prey or competitors (Carcinus maenas [Green Crab], Mytilus edulis [Blue Mussel], and Littorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…Jensen & Jensen [273] found that younger C. maenas in the Danish Wadden Sea favor the common cockle, Cerastoderma edule, over other prey items. Scherer & Reise [249] found that older males continue to feed on molluscs but older females feed primarily on annelid worms, although Baeta et al [262] found that different age classes and sexes of C. maenas showed no difference in diet when they occurred in the same area of an estuary in Portugal. More research should be done in the topic of differential feeding by different size classes, as it could be utilized for selective removal of certain size classes when trapping.…”
Section: Ecosystem Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jensen & Jensen [273] found that younger C. maenas in the Danish Wadden Sea favor the common cockle, Cerastoderma edule, over other prey items. Scherer & Reise [249] found that older males continue to feed on molluscs but older females feed primarily on annelid worms, although Baeta et al [262] found that different age classes and sexes of C. maenas showed no difference in diet when they occurred in the same area of an estuary in Portugal. More research should be done in the topic of differential feeding by different size classes, as it could be utilized for selective removal of certain size classes when trapping.…”
Section: Ecosystem Dynamicsmentioning
confidence: 99%
“…Individuals can be counted directly along a transect or within quadrats (see for example [52,105,125,145,248]) but this method is practical only for the intertidal zone at low tide (where mostly juveniles will be found) or in very shallow water. Extremely high densities of small juvenile crabs ranging from 200-2000 m −2 have been estimated using this method [95,109,249,250]. Divers can count crabs in subtidal areas but the type of vegetated or rocky bottom that offers suitable refuge also makes crabs very difficult to see.…”
Section: Population Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Four of the most commonly used methods are discussed here; a review of additional methods can be found in [64]. Individuals can be counted directly along a transect or within quadrats (see for example [37,87,90,109,134]) but this method is practical only for the intertidal zone at low tide where mostly juveniles will be found or in very shallow water. Extremely high densities of small juvenile crabs ranging from 200 -2000 m -2 have been estimated using this method [72,[135][136][137].…”
Section: Population Densitymentioning
confidence: 99%
“…sanguineis has essentially eliminated C. maenas in the rocky intertidal zone where it formerly was extremely abundant [134,233,[235][236][237][238][239][240] and apparently the same thing happened along the Delaware coastline [241]. In the presence of H. sanguineus, C. maenas not only occupies a less-desirable habitat but also alters its diet from bivalves, its preferred prey, to consume more algae [211].…”
Section: Competitorsmentioning
confidence: 99%